Development of a pheromone monitoring system for the goosefoot groundling moth, Scrobipalpa atriplicella (von Röslerstamm) in quinoa, Chenopodium quinoa (Willdenow). (March 2023) - Hussain, Altaf; Hladun, Shane; Vincent, Marc; Wist, Tyler J.; Hillier, N. Kirk; Mori, Boyd A.
Abstract: The goosefoot groundling moth, Scrobipalpa atriplicella, (Lepidoptera: Gelechiidae) is a serious pest of quinoa, Chenopodium quinoa, in North America and Europe. Previous studies found male S. atriplicella were attracted to a generic pheromone lure containing ( Z )-5-dodecenyl acetate. Here, we identified further candidate sex pheromone components from female pheromone glands using gas chromatography-electroantennographic detection. We confirmed ( Z )-5-dodecenyl acetate to be an antennally active compound, and identified a previously unidentified minor component, ( E )-5-dodecenyl acetate. Field tests confirmed males were most attracted to a two-component blend in a 95:5 ratio of ( Z )-5-dodecenyl acetate to ( E )-5-dodecenyl acetate. We found that the 95:5 major to minor ratio captured more S. atriplicella moths and the lowest number of non-target noctuid moths compared to other ratios tested. The number of S. atriplicella captured varied with trap type, but not the two heights tested (0.5 and 1 m), however, we recommend pheromone-baited wing traps deployed at either at 0.5 or 1 m heights to reduce the possibility of trap saturation with sticky traps with smaller surface areas. These findings allow for future development of a pheromone-based monitoring program for this significant pest of quinoa in Canada. Highlights: Goosefoot groundling moth is a serious pest of quinoa in North America. Male moths are attracted to pheromones released by female moths. Pheromone components, rations and their deployment techniques drive the overall success of the lure.